ASSOCIATION BETWEEN ANXIETY-DEPRESSIVE SPECTRUM DISORDERS AND JOINT DISEASE IN WOMEN - A. O. Vasilyeva; P. A. Shesternya; M. M. Petrova (Научно-практическая ревматология, 2018)
The frequency of anxiety-depressive spectrum disorders (ADSDs) in patients with rheumatic diseases (RDs) is much higher than that in the general population. ADSDs are known to be associated with pain intensity, disease activity, and functional limitations. However, the majority of available papers are limited by the framework of a certain disease. Objective: to investigate the association of ADSDs with the characteristics of joint damage beyond the nosological approach. Subjects and methods. The investigation enrolled 38 women aged 18 years and older who had different RDs and preserved reproductive function, were treated at round-the-clock hospitals, and had no clinically significant comorbid diseases. All the patients were divided into two subgroups: 1) those with predominant hand joint injury and 2) those with joint involvement at other sites. All the patients were evaluated for disease activity (DAS-28-ESR, ASDAS-ESR), pain (visual analogue scale), and functional status (HAQ). The Hospital Anxiety and Depression Scale (HADS) was used to detect ADSDs and the Hamilton Anxiety Rating Scale (HAM-A) and the Hamilton Depression Rating Scale were employed to rate the severity of anxiety and depression, respectively. Results and discussion. The frequency of anxiety disorders evaluated through the HADS and the HAM-A was 44.7 and 34.2%, that of depressions was 34.2 and 60.5% respectively. The clinically evident level of HADS anxiety (11+) in Subgroup 1 was detected 5 times more frequently (30.0%) than in Subgroup 2 (5.5%); and that of HAM-A anxiety (18+) was twice as often: 45.0 and 22.2%, respectively. The frequency of clinically significant depression according to HADS (11+) and HAM-D (14+) in Subgroup 1 was 30.0 and 40.0%, and that in Group 2 was 11.1 and 16.7% respectively. The probability of severe depressions (HAM-D 19+) in hand joint injury was twice higher (odds ratio, 2.2; 95% confidence interval, 1.51–3.19) than in arthritis at various sites. Thus, this investigation provides evidence for the high frequency of ADSDS in patients with RDs. Reproductive-aged women with hand joint injury are one of the most vulnerable groups.